2020
DOI: 10.5812/ijpbs.101535
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Exposure/Response Prevention plus Eye Movement Desensitization and Reprocessing in Reducing Anxiety and Obsessive-Compulsive Symptoms Associated with Stressful Life Experiences: A Randomized Controlled Trial

Abstract: Background: Obsessive-compulsive disorder (OCD) is known as a non-psychotic mental disorder resistant to treatment. It has been found that eye movement desensitization and reprocessing (EMDR) can increase the effectiveness of its standard treatments. Objectives: The current study aimed at evaluating the impact of exposure/response prevention (ERP) combined with EMDR as a treatment method on patients with OCD who had experienced stressful life events by comparison to ERP alone. Methods: The present randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…All 13 articles reporting CBT use included RCTs in which patients who received standard CBT had lower Y-BOCS scores post-treatment than pre-treatment compared to control conditions, all of which were psychotherapeutic interventions (35% to 93.8% of responders had significantly improved obsessive compulsive symptoms according to Y-BOCS scores). In these 13 studies, CBT was compared to the following control interventions: supportive therapy 58 (PEDro score = 9); self-help 57 (CBT Cohen’s d = 3.75; self-help Cohen’s d = 0.77, and waiting list Cohen’s d = -0.11) (PEDro score = 9); eye movement desensitization and reprocessing 30 ( η 2 = 0.296) (PEDro score = 6); acceptance and commitment therapy 36 (ERP: Cohen’s d = 2.498, and acceptance and commitment therapy + ERP (Cohen’s d = 0.113) (PEDro score = 10); danger ideation reduction therapy 37 (danger ideation reduction therapy pre- and post-treatment comparison: Cohen’s d = 1.811; ERP pre and post-treatment comparison: Cohen’s d = 4.801) (PEDro score = 8); and an inference-based approach 40 (Cohen’s d = 0.3) (PEDro score = 9). Two of these studies tested mindfulness (Kulz et al 55 : η 2 p = 0.053; p = 0.036; Rupp et al 29 : Cohen’s d = 0.53) (PEDro score = 9; 11) and another tested “association splitting” vs. cognitive remediation 54 ( η 2 p = 0.024) (PEDro score = 8) as add-on therapies, although none of the results supported the effectiveness of these treatment options; all tested interventions differed from CBT without significant effect sizes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 13 articles reporting CBT use included RCTs in which patients who received standard CBT had lower Y-BOCS scores post-treatment than pre-treatment compared to control conditions, all of which were psychotherapeutic interventions (35% to 93.8% of responders had significantly improved obsessive compulsive symptoms according to Y-BOCS scores). In these 13 studies, CBT was compared to the following control interventions: supportive therapy 58 (PEDro score = 9); self-help 57 (CBT Cohen’s d = 3.75; self-help Cohen’s d = 0.77, and waiting list Cohen’s d = -0.11) (PEDro score = 9); eye movement desensitization and reprocessing 30 ( η 2 = 0.296) (PEDro score = 6); acceptance and commitment therapy 36 (ERP: Cohen’s d = 2.498, and acceptance and commitment therapy + ERP (Cohen’s d = 0.113) (PEDro score = 10); danger ideation reduction therapy 37 (danger ideation reduction therapy pre- and post-treatment comparison: Cohen’s d = 1.811; ERP pre and post-treatment comparison: Cohen’s d = 4.801) (PEDro score = 8); and an inference-based approach 40 (Cohen’s d = 0.3) (PEDro score = 9). Two of these studies tested mindfulness (Kulz et al 55 : η 2 p = 0.053; p = 0.036; Rupp et al 29 : Cohen’s d = 0.53) (PEDro score = 9; 11) and another tested “association splitting” vs. cognitive remediation 54 ( η 2 p = 0.024) (PEDro score = 8) as add-on therapies, although none of the results supported the effectiveness of these treatment options; all tested interventions differed from CBT without significant effect sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Group or individual CBT therapy was proven to be as or more effective than other psychological treatments, such as mindfulness, 29 acceptance and commitment therapy, 36 or EMDR. 30 The number of weekly sessions ranged from 12 to 16, lasting from 60 to 120 minutes each, except intensive treatment (24), in which 4 to 8 hours of treatment were provided on 4 consecutive days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that both groups significantly reduced OCD symptoms at posttreatment and 6-month follow-up, and that there were no differences between the EMDR and ERP groups. Similarly, Sarichloo et al (2020) compared the effectiveness of EMDR combined with ERP (EMDR + ERP) and ERP alone on a sample of medication-resistant OCD patients with a history of trauma. They found that although both groups resulted in a reduction of OCD symptoms, the EMDR + ERP group was more effective in reducing symptoms.…”
Section: Group Studiesmentioning
confidence: 99%